Strengthening Integrated Learning through Data-Based Planning in the Implementation of the Independent Curriculum: A Case Study of an Elementary School - Taslim Buaja; Sumarni Sahjat Karomi; Amirudin Ais (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to analyze how Data-Based Planning supports evidence-based decision-making and improves the implementation of the Independent Curriculum at State Elementary School 65 West Halmahera. The study also examines how data utilization contributes to more effective learning planning and continuous school improvement. Methodology: This study employed a descriptive qualitative case study approach. Data were collected through semi-structured interviews with the principal and teachers, classroom observations, and document analysis, including the School Work Plan, Education Report Card, and other planning documents. The collected data were analyzed using descriptive qualitative analysis. Main Findings: The findings indicate that the systematic use of academic and non-academic data enables schools to identify learning problems, develop more appropriate instructional strategies, and improve school planning based on actual needs. Data-Based Planning also strengthens teacher collaboration, encourages reflective practices, and supports continuous improvement in implementing the Independent Curriculum. Novelty/Originality of this study: This study provides empirical evidence on implementing Data-Based Planning through the Identification–Reflection–Improvement framework in an elementary school. The findings demonstrate that Education Report Card data can support collaborative planning, evidence-based decision-making, and sustainable school improvement, offering practical insights for strengthening integrated learning implementation in primary education.